Breach: Host Membrane Penetration and Entry by Nonenveloped Viruses. Issue 6 (June 2018) - Kumar, Chandra Shekhar; Dey, Debajit; Ghosh, Sukanya; Banerjee, Manidipa
Abstract : Disruption of host membranes by nonenveloped viruses, which allows the nucleocapsid or genome to enter the cytosol, is a mechanistically diverse process. Although the membrane-penetrating agents are usually small, hydrophobic or amphipathic peptides deployed from the capsid interior during entry, their manner of membrane interaction varies substantially. In this review, we discuss recent data about the molecular pathways for externalization of viral peptides amidst conformational alterations in the capsid, as well as mechanisms of membrane penetration, which is influenced by structural features of the peptides themselves as well as physicochemical properties of membranes, and other host factors. The membrane-penetrating components of nonenveloped viruses constitute an interesting class of cell-penetrating peptides, and may have potential therapeutic value for gene transfer. Highlights: Cellular membrane penetration by nonenveloped viruses is carried out by membrane-active amphipathic or hydrophobic peptides that are internal components of the capsid. Similarities exist between how the peptides are generated, their exposure from the capsid, and eventual deployment, although there are dissimilarities in their modes of membrane penetration. Structures of dynamic disassembly intermediates provide information about the mechanistic details of peptide exposure and membrane interaction. Each intermediate likely represents a collation of subtly different conformational states in the disassembly pathway. Peptides trigger membrane damage by varied methods such as pore/channel formation, osmolysis, or induction of membrane curvature. The exact mode of membrane–peptide interaction may depend on the physicochemical properties of the membrane, as well as on other host factors.